Keteladanan Akhlak Khulafaur Rasyidin Dalam Pengembangan Karakter Muslim - Diva Dhiyaul Auliyah; Rosaliana Rosaliana; Sevia Rahayu Nur Habibah; Mahfud Ifendi (Yayasan Miftahul Ulum Sangatta Kutai Timur (KEP. MENKUMHAM RI No. AHU-0014779.AH.01.04.Tahun 2018) bekerjasama dengan Jurusan Tarbiyah STAI Sangatta Kab. Kutai Timur., 2024)
The example and positive values of Khulafaur Rashidin are very important in developing Muslim character. The example of Khulafaur Rasyidin is a reference or source for Muslims in developing good character and behaviour in accordance with Islamic teachings. The purpose of the research is to find out how the implementation of the moral values of Khulafaur Rasyidin can affect the behaviour of Muslims in everyday life and how the role of Islamic education and society in supporting the process of Muslim character building that prioritises the moral values of Khulafaur Rasyidin. The method used by researchers is a qualitative research method with a type of library research that collects data by understanding and studying theories and various literature related to the research. using main objects such as books or various literature sources. The results of this study are that 1). The implementation of the moral values of Khulafaur Rashidin is very important so that Muslims can create an environment that supports moral and spiritual development, and makes a positive contribution to the sustainability of society. 2). The importance of Islamic education and society in shaping good character and morals in a community environment that prioritises the moral values of Khulafaur Rashidin.